Formulation, Optimization and Evaluation of Luteolin-Loaded Topical Nanoparticulate Delivery System for the Skin Cancer - Imran Kazmi; Fahad A. Al-Abbasi; Muhammad Shahid Nadeem; Hisham N. Altayb; Sultan Alshehri; Syed Sarim Imam (MDPI AG, 2021)
In the present study, luteolin (LT)-loaded nanosized vesicles (LT-NVs) were prepared by a solvent evaporation-hydration method using phospholipid and edge activator. The formulation was optimized using three factors at a three-level Box-Behnken design. The formulated LT-NVs were prepared using the three independent variables phospholipid (A), edge activator (B) and sonication time (C). The effect of used variables was assessed on the vesicle size (Y1) and encapsulation efficiency (Y2). The selection of optimum composition (LT-NVopt) was based on the point prediction method of the software. The prepared LT-NVopt showed the particle size of 189.92 ± 3.25 nm with an encapsulation efficiency of 92.43 ± 4.12% with PDI and zeta potential value of 0.32 and −21 mV, respectively. The formulation LT-NVopt was further converted into Carbopol 934 gel (1% w/v) to enhance skin retention. LT-NVoptG was further characterized for viscosity, spreadability, drug content, drug release, drug permeation and antioxidant, antimicrobial and cytotoxicity assessment. The evaluation result revealed optimum pH, viscosity, spreadability and good drug content. There was enhanced LT release (60.81 ± 2.87%), as well as LT permeation (128.21 ± 3.56 µg/cm2/h), which was found in comparison to the pure LT. The antioxidant and antimicrobial study results revealed significantly (p ˂ 0.05) better antioxidant potential and antimicrobial activity against the tested organisms. Finally, the samples were evaluated for cytotoxicity assessment using skin cancer cell line and results revealed a significant difference in the viability % at the tested concentration. LT-NVoptG showed a significantly lower IC50 value than the pure LT. From the study, it can be concluded that the prepared LT-NVoptG was found to be an alternative to the synthetic drug as well as conventional delivery systems.